The Use of Palynology in Sequence Stratigrafy Analysis a Case Study, The Eocene Nanggulan Formation - Eko Budi Lelono (Scientific Contributions Oil and Gas, 2000)
This paper is a part of palynological investigationon The Eocene Nanggulan Formation, Yogjakarta Central Java. The NanggulanÂ Formation containing rich palynomorph assemblage provider excellent data to support sequence stratigraphy analysis. TheÂ palynomorph assemblage changes (especially between mangrove and freshwater palynomorphs) may reflect sea level changes whitch can be used to interpret system tracts, which are the internal building blocks of sequences.